Bono's Product (RED) initiative: wedding hard commerce and corporate social responsibility - Stefano Ponte; Lisa Ann Richey; Mike Baab (Danish Institute for International Studies (DIIS), 2008)
Bono's Product (RED) initiative was created to raise awareness and money for The Global Fund to Fight AIDS, Tuberculosis and Malaria by teaming up with major corporations to market RED co-branded products. RED has been built upon the principle that 'hard commerce' can be an appropriate vector for raising funds for good causes that are usually presented under the umbrella of Corporate Social Responsibility (CSR). In this paper, we examine how the corporations that have joined the RED initiative (American Express, Apple, Armani, Converse, Gap, Hallmark, and Motorola) use it not only to build up their brand profiles, sell products, and/or portray themselves as both as caring and cool, but also to address some of the key challenges in the hard commerce environment they face daily. In the process, they are moving the boundaries of CSR away from addressing the problematic aspects of their own operations and towards solving the problems of others who are 'distant' beneficiaries. We argue that RED can improve a corporation's brand without challenging any of its actual practices. In so doing, it fits neatly in a framework of 'win-win' representations of the role of business in society and, at the same time, helps companies to re-focus on their financial bottom line, which is especially important in the current period of slimming corporate profits and slower growth. With RED, 'doing good' becomes a fashionable accessory of brand management and the practices of hard commerce.
Keywords: 330; Corporate Social Responsibility; Wirtschaftsethik; Markenpolitik; Welt